2008
DOI: 10.1016/j.jacc.2008.08.052
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Adenosine Overcomes the Attenuation of Myocardial Perfusion Reserve Caused by Caffeine

Abstract: Caffeine in coffee attenuates adenosine-induced coronary hyperemia and, consequently, the detection of perfusion abnormality by adenosine MPS. This can be overcome by increasing the adenosine dose without compromising test tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 22 publications
2
32
0
2
Order By: Relevance
“…4,5 In these two studies, average plasma caffeine concentration was half the concentration attained in the only study documenting a positive effect. 6 Of note, the levels of caffeine detected in this study were close to those reported in the early dipyridamole work. In all three studies, caffeine did not appear to affect the hemodynamic response to adenosine stress.…”
supporting
confidence: 87%
“…4,5 In these two studies, average plasma caffeine concentration was half the concentration attained in the only study documenting a positive effect. 6 Of note, the levels of caffeine detected in this study were close to those reported in the early dipyridamole work. In all three studies, caffeine did not appear to affect the hemodynamic response to adenosine stress.…”
supporting
confidence: 87%
“…56,59 It is unclear whether the degree of attenuation of the magnitude of coronary hyperemia caused by caffeine would result in a clinically significant change to myocardial perfusion results. 60 A number of studies have investigated the effects of caffeine consumption on the MPI results using adenosine stress finding some effect on imaging, 61 but often no significant effect. 62,63 The data on regadenoson are somewhat mixed with an animal study reporting that caffeine did not affect the maximum increase in Table 5.…”
Section: Caffeine and Coronary Vasodilatorsmentioning
confidence: 99%
“…Inter-individual variation in the response to adenosine is well reported 24 and significant reductions in heart rate response are seen when adenosine infusion is repeated after caffeine intake. 25 However, in this study, it may be that familiarization with the protocol meant that subjects were less anxious during the second administration of adenosine. This change in RPP could explain the trend towards reduced stress perfusion between Scans 1 and 2 but does not account for the trend towards reduced rest perfusion.…”
Section: Discussionmentioning
confidence: 85%